A Systematic Integrative Review of Aerobiological Investigations Related to Arachis hypogaea L. Cultivation in Dhule, Maharashtra (International Journal of Scientific Research in Science and Technology, 2025)
Aerobiology focuses on understanding the behaviour and distribution of biological particles, or air spora, suspended in the atmosphere, including plant fragments, spores, dust, and animal remnants. Groundnuts emerge as a vital crop in this discussion, prized not only for their nutritional value but also for their versatility in producing oil and organic fertilizer. This field expands into specialized studies like aeropalynology and aeromycology, which examine pollen and fungal spores respectively—elements that have significant implications for public health, particularly through allergies. Recent interdisciplinary efforts in medical paleontology are exploring how controlled exposure to certain fungal allergens might offer therapeutic benefits. Research findings consistently reveal that fungal spores, often originating from genera such as Puccinia, Aspergillus, and Rhizopus, predominate in the airborne particle mix, especially during humid harvest periods. Climatic factors such as temperature, humidity, and vegetation maturity play a crucial role in influencing spore concentrations, as seen in studies across regions like Solapur. Hydroponic groundnut cultivation is revolutionizing agricultural yields by utilizing cost-effective and less labour-intensive techniques. Regions like Dhule in Maharashtra, with their unique semi-arid environment and high agricultural activity, underscore the urgent need for further aerobiological research to enhance both public health and crop productivity.